Adrenal insufficiency resulting from immunotherapy: a rare but life-threatening side effect - Shaharudin, Muhammad Yusuf; Zulkhairi, Mohammad (International Journal of Basic & Clinical Pharmacology, 2021)
A 73-year-old male whom suffers from stage 4 adeno-squamous lung carcinoma with high programmed death-ligand 1 (PD-L1 immunohistochemistry-tumor proportion score (TPS)>50 began his treatment with a type of immune checkpoint inhibitors (ICI) therapy. After 8th cycle of treatment, patient experiences vague symptoms of fever, lethargy and drowsy. Initial working diagnosis was infection and empirical treatment was initiated. Subsequently as patient’s condition did not improve despite appropriate antibiotics, other diagnosis was considered which include adrenal insufficiency and this confirms after checking cortisol level. Hydrocortisone was started promptly and patient clinical condition improved. Decision was to stop ICI treatment interim. Consideration to re-challenge again with ICI may be considered once patient is more fit in the future. Adrenal insufficiency following ICI treatments are rare and misdiagnosed due to its non-specific symptoms. Nonetheless, it comes with high morbidity and mortality. Hence, we wanted to emphasize more on this condition as more elderly patients whom suffers from various type of cancers will be exposed towards ICI treatment.